'Managing the transition' : supplier management in international joint ventures in China - Zhang, Lihong; Goffin, Keith (Emerald Group Publishing Limited, 2001)
Attracted by the easier access to local markets, many foreign companies have formed manufacturing joint ventures in China. One of the key elements of successful international joint venture (IJV) manufacturing in China is the management of suppliers, since the supply chain plays an essential role in contributing to both the quality of finished products and controlling costs. Supplier management in Chinese IJVs is an under-researched area and so an exploratory study of five manufacturers was conducted using a case study approach. The results show the difficulties faced by IJVs which are in attempting to maintain quality levels at the same time as trying to reduce costs by purchasing materials and components locally. In addition to identifying important implications for companies, the research shows the need for further investigation of the contextual aspects of good supplier management.
Keywords: China; International manufacturing; Joint ventures; Supplier relations